Terapia de emissão de luz por diodo induz analgesia em modelos de nocicepção em camundongos: análise do mecanismo de ação - Pigatto, Glauce Regina (2015)
The LEDT is a fairly recent category of phototherapy and there is evidence that accelerates wound healing, reduce inflammation and painful. However, there are few scientific studies on the action mechanisms of LEDT in pain control. In this sense, the present study aimed to evaluate the antinociceptive effect of LEDT in models of acute pain, as well as to investigate the possible mechanism adjacent to this effect in mice. For the experiments Swiss adult female mice were used (25 to 35 g) with about 2 months old. The LEDT applied 20 minutes before the experiments (890 nm, 390 mW, 20.8 J/cm²), promoted reduction of the nociceptive neurogenic (1nd phase) and inflammatory pain (2nd phase) and paw oedema induced by intraplantar (i.pl.) injection of formalin. LEDT also prevented nociception induced by intraperitoneal injection of acetic acid. Furthermore, LEDT (20.8 J/cm²) prevented nociception induced by i.pl. injection of capsaicin [activator of transient receptor potential vanilloid-1 (TRPV1)], cinnamaldehyde [activator of transient receptor potential ankyrin-1 (TRPA1)], menthol [activator of transient receptor potential melastatin-8 (TRPM8)], acidified saline activator of acid sensitive ion channels (ASICs)] and glutamate (activator of ionotropic and/or metabotropic glutamate receptors). Centrally, LEDT increased the latency to nociceptive stimulation in the hot plate model. Moreover, the opioid system is involved in the mechanism of action of LEDT, since its was reversed by naloxone a nonselective opioid receptor antagonist). It has been demonstrated also the involvement of the adenosinergic system since its effect was reversed by caffeine (a nonselective adenosine receptor antagonist), DPCPX (A1 receptor antagonist) and ZM 241385 (A2A receptor antagonist) and via L-arginine/nitric oxide, which the LEDT effect was reversed by L-arginine (a precursor of nitric oxide) and not by D-arginine (inactive isomer of L-arginine). Additionally, LEDT was able to prevent nociception induced by PLC/PKC and cAMP/PKA pathway activators, PMA, BK, forskolin and PGE2. Intrathecal treatment with capsaicin (for desensitization of C fibers) changed the nociceptive response of formalin and the desensitization of Antinociceptive effect influenced LEDT. Taken together, the results show that the antinociceptive effect of LEDT is due, in part, by involvement of the opioid system, adenosinergic, L-arginine/NO pathway and inhibition of glutamatergic system, and TRPV1, TRPA1, TRPM8 and ASICs channels, as well as the PLC/PKC and/or cAMP/PKA signaling-dependent inhibition. Thus, the results of this study support that LEDT has potential effect on pain control, and the continuity of preclinical studies and suggest that this therapy can be a useful complement to the treatment of pain of different etiologies.